2020
DOI: 10.1155/2020/5357329
|View full text |Cite
|
Sign up to set email alerts
|

Is the Recurrence of Fibroma of the Tendon Sheath Underestimated? An Instructive Case Report and a Review of the Literature

Abstract: We report a case of a 21-year-old healthy woman with a history of a painful growing mass in the palm of the right hand, with a trigger finger phenomenon. The mass was surgically entirely excised, and the histological findings of the tumor were those of a fibroma of the tendon sheath (FTS) starting from the flexor tendons. Although the initial outcome was good, the patient experienced the same symptoms at the same location 4.5 years later. The MRI demonstrated a 50 × 10 × 5 mm mass of low intensity on T1-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In 1979, Chung and Enzinger reported that the local recurrence rate in 40 patients was 24% at a mean followup of 4.3 years after surgical excision [4]. Since then, many studies have reported low or zero local recurrence rates, but these rates may be artifactual because of inadequate follow-up periods [21,27]. In our case, marginal resection was performed carefully using an air tourniquet and a surgical loupe to reduce the risk of local recurrence.…”
Section: Discussionmentioning
confidence: 76%
“…In 1979, Chung and Enzinger reported that the local recurrence rate in 40 patients was 24% at a mean followup of 4.3 years after surgical excision [4]. Since then, many studies have reported low or zero local recurrence rates, but these rates may be artifactual because of inadequate follow-up periods [21,27]. In our case, marginal resection was performed carefully using an air tourniquet and a surgical loupe to reduce the risk of local recurrence.…”
Section: Discussionmentioning
confidence: 76%